Gender Representation in Rwandan Music Videos. Issue 2 (3rd April 2022) - Rwubaka, Tessa Djamilla; Prieler, Michael
Abstract: This study analysed gender representations in a sample of 100 Rwandan music videos. Some of our findings were in accordance with those of previous studies focusing on other countries, including the findings that in videos men clearly outnumber women and women are sexually objectified through the use of clothing, gaze, partialising, and sexually suggestive movements. However, in contrast to previous literature on music videos in Western countries, this study on Rwandan music videos found hardly any violence or aggression in the videos and hardly any age differences between the men and women represented. Reasons for these results are discussed as well as the potential effects of such representations, including the objectification of women and an acceptance of gender role stereotypes.